Percutaneous interventions in cardiology in Poland in the year 2014. Summary report of the Association of Cardiovascular Interventions of the Polish Cardiac Society AISN PTK - Ochała, Andrzej; Siudak, Zbigniew; Legutko, Jacek; Parma, Radosław; Chmielak, Zbigniew; Bartuś, Stanisław; Dobrzycki, Sławomir; Grygier, Marek; Moszura, Tomasz; Pawłowski, Tomasz; Dudek, Dariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : The Board of the Association of Cardiovascular Interventions of the Polish Cardiac Society (AISN PTK) publishes annual data from the National PCI Registry (ORPKI) operated by the Jagiellonian University Medical College in Krakow. Aim : For the first time the AISN PTK report is based on the new electronic database implemented in Poland on January 1st, 2014. Material and methods : In 2014, there were 155 invasive cardiology centers registered in the ORPKI database (an increase by 1 center in comparison to 2013) and 92% of them had 24/7 percutaneous (PCI) duty. For the first time the number of catheterization laboratories (cath labs) in Poland remained stable, and even though there was an increase by 1 in absolute numbers, 2 cath labs ceased to admit patients in 2014. This means that the number of active cath labs per 1 million inhabitants is similar to last year and equals 4. Results : In comparison to 2013, there was a significant increase in the total number of coronary angiographies. There were 226 713 angiographies in 2014. The total number of PCI procedures was 126 241, which is 5.1% more than in 2013. Conclusions : There was a significant increase in the overall number of coronary angiographies and PCIs in Poland in 2014. The use of attributes of modern interventional cardiology such as drug-eluting stents and bioabsorbable vascular stents is growing as well as more frequent choice of a radial access site by PCI operators even in ST-elevation myocardial infarction patients. One should also note a significant rise in the use of additional imaging or diagnostic tools such as fractional flow reserve, intravascular ultrasound and optical coherent tomography.